An annotated catalogue of the Iranian Tingidae (Hemiptera: Heteroptera) - Ghahari, Hassan; Montemayor, Sara I.; Moulet, Pierre; Linnavuori, Rauno E. (Zootaxa, 2012)
An updated list of Iranian Tingidae Laporte is presented and discussed in this paper. For Iranian fauna, there are recordsof 74 species and subspecies of tingids distributed in 20 genera and subgenera, of which 72 of them belong to the subfam-ily Tinginae and 2 species to the subfamily Cantacaderinae (tribe Cantacaderini). In some species we list host plants, in Iran.